العلامة محمد باي بلعالم وآراؤه العقدية - شيباني, يوسف (University of Eloued-جامعة الوادي, 2022)
"ملخص الدارسة باللغة العربية: سلطت الضوء من خلال دراستي ”العلامة محمد باي بلعالم آراؤه العقدية ‟في إبراز شخصية الشيخ الفقيه العالم العلامة والتعريف به وبجهوده العقدية في شرح مباحث العقيدة الإسلامية ومسائلها وفروعها (الإلهيات-النبوءات- السمعيات) وجمعها وسردها في رسالة علمية واحدة. ""Study summary in english: I shed light through my study “Allamah Muhammad Bay Belalem Doctrinal Views” in highlighting the personality of the scholar-faqih, the scholarly scholar and introducing him and his doctrinal efforts in explaining the topics of the Islamic faith, its issues and its branches (theology – prophecies – audio), collecting and narrating them in one scholarly treatise"
مذكرة ماستر
Keywords: العلامة محمد باي بلعالم - آراؤه العقدية; Allama Muhammad Bay Belalem - His Doctrinal Views